PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN PEEMBELAJARAN MATEMATIKA KELAS III SEKOLAH DASAR - Fitia Amalina; Hannisa Haris; Muhammad Syahrul Rizal; Moh. Fauziddin; Nurmalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this research is the low understanding of the concept of multiplication in mathematics learning of grade III students. This study aims to improve the ability to understand the concept of socialization of class III students of SDN 003 Bangkinang. This study is a classroom action research (CAR) which is carried out in two cycles and each cycle consists of two meetings. The subjects in this study were all class III students totaling 26 students. Data collection techniques were in the form of observation, documentation and tests. While the data analysis technique used was a combination of quantitative data and qualitative data. Based on the results of cycle 1, there were 11 students who completed the study with a percentage of 42.30% with an overall average of 67.88 and at the second meeting it increased to 14 students with a percentage of 53.84% with an overall average of 72.19. While in cycle II, meeting I, there were 19 students who completed the study with a percentage of 73.07% with an overall average of 77.42 and there was an increase at the second meeting to 24 students with a percentage of 92.30% with an overall average of 87.80. Based on the results of this study, it shows that by applying Contextual Teaching and Learning learning, (CTL) can improve the understanding of mathematical multiplication concepts of grade III students at SDN 003 Bangkinang.